2020
DOI: 10.3390/cancers13010081
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Participation Rates of the National Cancer Screening Program among Cancer Survivors in Korea

Abstract: The study aimed to describe the participation rates of the National Cancer Screening Program (NCSP) among cancer survivors in Korea. The NCSP protocol recommends that all Korean men and women should be screened for cancer. Cancer survivors were defined as those registered for any cancer in the Korea Central Cancer Registry by December 31 of the year prior to being included in the target population of the NCSP. In this study, the participation rates for the NCSP were calculated as the percentage of people who p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…However, a study that evaluated the trend of cancer survivors in the Korean National Cancer Screening Program found the screening rate among cancer survivors over 10 years (2022-2014) to be increasing (stomach cancer, 50.3%; breast cancer, 49.7%; cervical cancer, 45.2%; and colorectal cancer, 28.0%). [40] These rates were still low, so SPC screening education and encouragement should be emphasized along with healthy behaviors. In this study, the SPC screening rates among controls and BCSs were 73.2% and 74.8%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…However, a study that evaluated the trend of cancer survivors in the Korean National Cancer Screening Program found the screening rate among cancer survivors over 10 years (2022-2014) to be increasing (stomach cancer, 50.3%; breast cancer, 49.7%; cervical cancer, 45.2%; and colorectal cancer, 28.0%). [40] These rates were still low, so SPC screening education and encouragement should be emphasized along with healthy behaviors. In this study, the SPC screening rates among controls and BCSs were 73.2% and 74.8%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…According to the National Cancer Screening Program (NCSP) in South Korea and our transplant program protocol, all transplant candidates undergo cancer screening [ 18 ]. We perform esophagogastroduodenoscopy (for patients aged ≥16 years), colonoscopy (for patients aged ≥40 years), and abdominal ultrasonography (USG).…”
Section: Methodsmentioning
confidence: 99%
“…A study on the trends in socioeconomic inequalities in cancer screening services in Korea reported that inequalities and inequities in participation in gastric and colorectal cancer screening were weakened after the implementation of the NCSP, however, reducing only out-of-pocket expenses for cancer screening may not completely eliminate the inequality [36]. Previous studies have identified health system-related characteristics as the cause of non-participation [37]. Another study reported that barriers to cancer screening included lack of time, lack of knowledge about cancer screening programs, physical disability or underlying disease, and logistic barriers [38].…”
Section: E P U B a H E A D O F P R I N Tmentioning
confidence: 99%